A game of timing and visibility - Lotker, Zvi; Patt-Shamir, Boaz; Tuttle, Mark R. (Games and economic behavior, 2008)
We consider the following abstraction of competing publications. There are n players in the game. Each player i chooses a point x i in the interval [ 0 , 1 ] , and a player's payoff is the distance from its point x i to the next larger point, or to 1 if x i is the largest. For this game, we give a complete characterization of the Nash equilibrium for the two-player game, and, more important, we give an efficient approximation algorithm to compute numerically the symmetric Nash equilibrium for the n-player game. The approximation is computed via a discrete version of the game. In both cases, we show that the (symmetric) equilibrium is unique. Our algorithmic approach to the n-player game is non-standard in that it does not involve solving a system of differential equations. We believe that our techniques can be useful in the analysis of other timing games.